(untitled) (Higher Education Politics and Economics, 2025)
Average salaries of college graduates are higher than salaries of those without degrees. However, the experience of graduating and out-earning the income requirements for in-kind or entitlement benefits like Medicaid, public assistance, Supplemental Nutritional Assistance Plan, and/or Section 8 housing vouchers are not taken into consideration in any mobility calculation nor are students prepared to lose their benefits. Teaching at an urban commuter school in a financially disadvantage borough, I have identified a gap in the research literature and supportive services for these low-income students. This opinion piece further describes the problem and highlights areas for future action and research.